2020
DOI: 10.21203/rs.3.rs-68468/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Innovative Pharmacology Curriculum for Medical Students: Promoting Higher Order Cognition, Learner-Centered Coaching, and Constructive Feedback Through A Social Pedagogy Framework

Abstract: BackgroundOngoing developments in medical education recognize the move to curricula that support self-regulated learning processes, skills of thinking, and the ability to adapt and navigate uncertain situations as much as the knowledge base of learners. Difficulties encountered in pursuing this reform, especially for pharmacology, include the tendency of beginner learners not to ask higher-order questions and the potential incongruency between creating authentic spaces for self-directed learning and providing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For example, in a clinical clerkship program, Koop and others [20] found that students who were required to submit a revised paper demonstrated a much higher level of peer-to-peer interactions and more task-focused discussions on an online platform. Moreover, the introduction of internet-based wiki assignments was also reported to be effective in changing medical students' use of self-directed learning strategies, such as feedback seeking, peer evaluation and maintenance of learning communities [21].…”
Section: Problems In Medical Students' Engagement With Online Discussionmentioning
confidence: 99%
“…For example, in a clinical clerkship program, Koop and others [20] found that students who were required to submit a revised paper demonstrated a much higher level of peer-to-peer interactions and more task-focused discussions on an online platform. Moreover, the introduction of internet-based wiki assignments was also reported to be effective in changing medical students' use of self-directed learning strategies, such as feedback seeking, peer evaluation and maintenance of learning communities [21].…”
Section: Problems In Medical Students' Engagement With Online Discussionmentioning
confidence: 99%
“…Eleven studies used multicomponent interventions [42,52,53,67,71,[89][90][91][92][93][94], and of these, seven focused on prescribing skills and four on clinical pharmacology knowledge. Among all seven studies on prescribing skills, the most common components included prescription writing exercises (4 studies) [42,53,71,89], case-based learning (3 studies) [90,91,94], and group discussions (3 studies) [42,53,71].…”
Section: Multicomponent Educational Interventionsmentioning
confidence: 99%
“…Three studies reported positive Kirkpatrick level 2c outcomes -statistically significant improvement in prescription writing and medication communication skills [53,71,94] and another reported retention of prescribing skills four years after the intervention (42). As for the four studies which examined the effectiveness of multicomponent educational interventions in the clinical pharmacology teaching [52,67,92,93], all four included a component of didactic teaching and reported at least one positive finding on Kirkpatrick level 1. Three of the studies also incorporated group learning in the format of group assignments or group discussions [52,92,93].…”
Section: Multicomponent Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This revolutionary shift in the curriculum would not only meet the requirement of global medical education standards but would also play a role in patient-oriented care in health care organizations 15 .To accommodate modern trends, several new modalities have also been adopted at our institute including problem-based learning, integrated seminars, student-directed learning, small group discussions, and formative assessments 16,17 .…”
Section: Introductionmentioning
confidence: 99%